Growth and physiological processes of young starfruit (Averrhoa carambola L.) plants under soil flooding - Ismail, Mohd Razi; Mohd Noor, Khuzaimah (Elsevier, 1996)
Soil flooding decreased leaf area and dry weight of young starfruit (Averrhoa carambola L) plants after 5 days from the start of flooding. Leaf senescence was promoted by soil flooding and all leaves abcised after 20 days of flooding. The changes in leaf water potential in flooded plants followed two distinct phases; the first where leaf water potential was maintained or increased relative to the control for a period of approximately 15 days, and the second phase involving a decline in leaf water potential. Stomatal resistance was increased 24 h after start of flooding. Photosynthetic rate declined with soil flooding, and reached the compensation point approximately 16 days from start of flooding. An investigation on the effect of post-flooding treatments showed growth was permanently impaired in plants pre-exposed to 14 days of soil flooding. An increase in flower number was associated with soil flooding. The recovery of stomatal resistance in plants flooded for 7 days occurred 3 days after soil drainage. Plants that were exposed to 14 days flooding showed decreased stomatal resistance after relief of the flooding, but did not reach the value of the control plants. The photosynthetic rate of flooded plants also showed signs of recovery after flood relief. The relationship between leaf water potential and stomatal resistance of flooded plants is examined.